The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1186/1476-7961-10-1
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of casein-specific IgE and IgG4 antibodies in cow's milk allergic children

Abstract: BackgroundCow's milk allergy is one of the most common food allergies among younger children. We investigated IgE antibodies to milk, and IgE and IgG4 antibodies to casein, α-lactalbumin and β-lactoglobulin in cow's milk allergic (CMA) and non-allergic (non-CMA) children in order to study their clinical usefulness.MethodsEighty-three children with suspected milk allergy (median age: 3.5 years, range: 0.8-15.8 years) were diagnosed as CMA (n = 61) or non-CMA (n = 22) based on an open milk challenge or convincin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 29 publications
2
47
2
1
Order By: Relevance
“…The antibody response to BLG from milk in healthy, nonmilk-allergic adults was characterized by relatively low levels of pan IgG antibodies, which mainly belonged to the IgG4 subclass, and with a large interindividual vari- The relatively high serum levels of IgG4 to BLG shown in the present study have also been indicated in previous studies [20,21] . It is probably a consequence of repeated exposure to the antigen due to milk consumption leading to a strong IgG4 subclass antibody response in these tolerant individuals [7,8] .…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The antibody response to BLG from milk in healthy, nonmilk-allergic adults was characterized by relatively low levels of pan IgG antibodies, which mainly belonged to the IgG4 subclass, and with a large interindividual vari- The relatively high serum levels of IgG4 to BLG shown in the present study have also been indicated in previous studies [20,21] . It is probably a consequence of repeated exposure to the antigen due to milk consumption leading to a strong IgG4 subclass antibody response in these tolerant individuals [7,8] .…”
Section: Discussionsupporting
confidence: 71%
“…Studies in the area of food allergy have reported different findings and, whilst foodspecific IgG4 has been shown to increase during successful oral immunotherapy [22,23] , there are conflicting data on whether or not specific IgG4 is higher in children with food allergy compared to nonallergic children. Recent data suggest that antibody responses may vary with the allergen, dose, and timing of exposure [20,[24][25][26] . Most studies on specific serum IgG responses to food proteins have investigated responses to egg, milk, and wheat proteins, which are 3 of the "big eight" food allergens, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many researchers have focused on β-LG with regard to oral tolerance induction [6-9]. However, in clinical practice, it is reported that casein, rather than β-LG, is the more dominant causal allergen in CMA [10, 11]. Casein is contained in various processed foods such as infant formulas; therefore, it is important to investigate the immunological properties of casein in these foodstuffs.…”
Section: Introductionmentioning
confidence: 99%
“…However, for those with Bos d 8 levels lower than the 95 % CDP, a high number of false negatives were observed, suggesting that an OFC should still be performed in these patients. In a study by Ito et al [11], investigators measured serum sIgE to CM extract and CM components in 83 children with suspected CM allergy, 61 diagnosed as allergic and 23 as non-allergic based on results of an open OFC or a convincing history. The CM allergic group showed higher levels of CM, Bos d 8, and betalactoglobulin (Bos d 5) sIgE than the non-allergic group.…”
Section: Milk Allergymentioning
confidence: 99%